Effect of phenotype switched Candida auris mono-culture and co-culture biofilms on the morphology, viability, and adhesion of hTERT TIGKs and ORL-48 cell lines - Zainal, Mukarramah; Mohd Sarmin, Nurul ‘Izzah; Ibrahim, Mohammad Johari; Cirillo, Nicola; Dashper, Stuart G.; Arzmi, Mohd Hafiz (Elsevier, 2025)
Objectives: This study aims to determine the paracrine effects of Candida auris phenotypic switching in mono- and co-culture with Staphylococcus aureus on oral epithelial homeostasis and oncogenic progression in phenotypically normal (hTERT TIGKs) and malignant (ORL-48) oral keratinocytes. Design: C. auris switched phenotype was scored using Phloxine B, and mono- and co-culture biofilms with S. aureus were developed. hTERT TIGKs and ORL-48 cell lines were independently seeded into 6-well and 96-well plates for dispase and viability test, respectively. The oral cell lines were exposed to phenotypically switched C. auris mono- and co-culture biofilm test cell growth medium (TCGM) for 24 h. Outcomes included cell morphology, metabolic activity/viability (CCK-8), and cell–cell adhesion (dispase assay). Results: Microscopic observation revealed that the biofilm induced damage and disrupted epithelial cell integrity in a paracrine manner. The mono- and co-culture TCGM suppressed the growth of normal cells while promoting the metabolic activity of cancer cells. The adhesion analysis of hTERT TIGKs indicated a strong intercellular cohesion, while ORL-48 cells downregulated intercellular adhesion and compromised cell-cell cohesion. Conclusion: C. auris biofilms promote the development of a malignant phenotype by regulating cell viability, promoting epithelial-mesenchymal transition, and adhesion in a switched generation-dependent manner.